Wearing steadfast material for gasometrical covering on base of titanium-chromium double carbide - Гулевець, В.Д.; Петриченко, С.О. (Proceedings of National Aviation University (archive), 2004)
The presented trybotechnical characteristics in the condition of composite material absence on base of the coniferous carbide of titanium-chromium with metallic relationship Fe–Cr and Fe–Ni.